Genetic Variability of Monkeypox Virus and Its Implications for Human Disease - AL-Azzawi, Mustafa Kareem; Khlaif, Salam Mohammed; Zubaidi, Nabaa Abbas (Antis-Publisher, 2024)
The genomic sequencing of Monkeypox virus (MPXV) isolates has offered crucial insights into the virus's genetic variability and population biology. This review provides a concise summary of the current state of MPXV genetics and phylogenetics, with a particular emphasis on the potential of a broader dataset to improve molecular diagnostic methods and inform the development of antiviral medicines and diagnostic tests. The virus's evolutionary biology, particularly its interactions with natural reservoir hosts, can be better understood through the investigation of genetic data, precise outbreak identification, and improved surveillance. The genetic diversity among genotypes of monkeypox, a rare zoonotic infection with clinical manifestations similar to smallpox, significantly influences the severity of the disease and its transmission. The objective of this investigation is to enhance the genetic information on MPXV, evaluate the correlation between genotypic variations and disease outcomes, and investigate the manner in which these distinctions influence the pathogenesis of monkeypox. It is emphasized in the research that a multidisciplinary approach is crucial for the advancement of vaccine development, drug discovery, and the comprehension of virus-host interactions. The results underscore the necessity of ongoing genetic and serological surveillance to mitigate the obstacles presented by monkeypox and enhance public health responses.